2019
DOI: 10.1002/jbt.22318
|View full text |Cite
|
Sign up to set email alerts
|

Brain region‐specific regulation of histone acetylation and efflux transporters in mice

Abstract: Multidrug resistance protein 1 (MDR1) and breast cancer resistance protein (BCRP) protect the brain by restricting the passage of chemicals across the blood-brain barrier. Prior studies have demonstrated the epigenetic regulation of MDR1 and BCRP in cancer cells treated with histone deacetylase (HDAC) inhibitors that enhance histone acetylation and gene transcription. In the present study, we tested the in vivo effects of two HDAC inhibitors, valproic acid (VPA; 400 mg/kg) and apicidin (5 mg/kg), on Mdr1 and B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…Furthermore, SCFAs were shown to induce Mdr1 mRNA in livers of male Sprague-Dawley rats following intraperitoneal doses of VPA and butyrate for 7 days (Eyal et al, 2006). Likewise, 7-day intraperitoneal treatment with VPA, a brain-penetrable HDAC inhibitor, significantly up-regulated the Mdr1 protein in the striatum of C57BL/6 mice along with levels of acetylated histone H3K9/14 (You et al, 2019a). Such in vivo data extend the in vitro findings and suggest that SCFA HDAC inhibitors can alter MDR1 expression in normal healthy tissues as well as cancer cell lines.…”
Section: Short Chain Fatty Acidssupporting
confidence: 72%
See 3 more Smart Citations
“…Furthermore, SCFAs were shown to induce Mdr1 mRNA in livers of male Sprague-Dawley rats following intraperitoneal doses of VPA and butyrate for 7 days (Eyal et al, 2006). Likewise, 7-day intraperitoneal treatment with VPA, a brain-penetrable HDAC inhibitor, significantly up-regulated the Mdr1 protein in the striatum of C57BL/6 mice along with levels of acetylated histone H3K9/14 (You et al, 2019a). Such in vivo data extend the in vitro findings and suggest that SCFA HDAC inhibitors can alter MDR1 expression in normal healthy tissues as well as cancer cell lines.…”
Section: Short Chain Fatty Acidssupporting
confidence: 72%
“…Several studies have delved deeper to delineate the mechanisms by which HDAC inhibitors alter efflux transporter expression in various cell types. These studies have consistently revealed a correlation between transporter regulation and alterations in the acetylation status of histones in response to HDAC inhibitors (Jin and Scotto, 1998;El-Osta et al, 2002;Baker et al, 2005;Tabe et al, 2006;El-Khoury et al, 2007;Kim et al, 2008;Hauswald et al, 2009;Kim et al, 2009;Valdez et al, 2016;You et al, 2019a;You et al, 2019b). Such association confirmed that HDAC inhibitors did in fact prevent the de-acetylation of histone proteins.…”
Section: Regulationmentioning
confidence: 86%
See 2 more Smart Citations
“…Concerning histone post-translational modifications, exposure to valproate increased acetylation of histone H4 in the ABCG2 promoter in CMK cells as well as ABCG2 mRNA levels [194]. A recent study demonstrated that treatment with histone deacetylase elicits brain region-specific enhancement of histone H3 acetylation and upregulation of ABCG2 transporter in mice [195].…”
Section: Modulation Of the Genes Encoding Transporters With Increamentioning
confidence: 99%